Implementation of Forward Chaining in a Web-Based Expert System for Diagnosing Chili Pepper Plant Diseases - Nur Istiqlaliyah; Eka Febriana Ishak; Fina Inayatul Maula; Talita Zada Aqila; Nur Hadian (LPPM & Fakultas Teknologi Informasi UNSAP, 2026)
Chili plants are among superior horticultural commodities with high economic value and play a crucial role in supporting the agricultural sector in Indonesia. In cultivation practices, chili productivity often declines due to infections caused by various plants diseases. This condition is futher exacerbated by farmers limited technical knowlegde and insufficient accsess to agricultural experts, which frequently caused delays in the diseases identification process. This study aims to develop a website based expert system to assist in diagnosing chili plant diseases by applying forward chaining method. The system operates by processing facts input by users to generate appropriate diseases diagnoses and teatment recommendations. The system’s knowlegde base was constructed through literature studies and interviews with agricultural experts, and was represented in the form of IF-THEN rules. The testing results indicate that the expert system is capable of accurately identifying types of diseases iaffecting chili plants and providing relevant handling recommendations. Therefore, the proposed system is expected to support chili farmers in making more effective decisions, thereby improving chili crop productivity.